ETNOBOTANI KAPUL (Baccaurea macrocarpa) DAN LIMPASU (Baccaurea lanceolata) OLEH SUKU DAYAK DAN SUKU BANJAR DI KABUPATEN HULU SUNGAI SELATAN DAN HULU SUNGAI TENGAH - Nor Hikmah; Gunawan Gunawan (Universitas Lambung Mangkurat, 2022)
The Dayak and Banjar people who generally live on the banks of the river often take advantage of forest product materials such as plants for the purpose of meeting food needs, customs and so on. This study reveals the use of Baccaurea macrocarpa and Baccaurea lanceolata by the Dayak and Banjar tribes in Hulu Sungai Selatan and Hulu Sungai Tengah districts. The study used the snowball sampling method, visiting and interviewing the community who were key respondents on a rolling basis and collecting data from informant discussions. The results showed that the Dayak and Banjar tribes traditionally still use the kapul and limpasu plants, the parts used are roots, stems, leaves and fruit, and the most used parts for the limpasu plants are 50% fruit, the most used kapul plants are 66 fruit parts. ,6%. These plants are used as complementary materials for processed foods, building materials, cosmetics, health drugs such as: fever medicine, internal heat, stomach pain, facial skin care, refreshing the body and treating the covid'19 virus. However, the current utilization is rarely carried out due to changes in land function such as land clearing for gardens and construction of houses, thus endangering plant habitats and the need for follow-up actions such as conservation activitiesÂ Keyword : Dayak Tribe, Banjar Tribe, Baccaurea macrocarva, Baccaurea lanceolata